2021
DOI: 10.3390/polym13101631
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Acetate-Based Electrospun Materials with a Variety of Biological Potentials: Antibacterial, Antifungal and Anticancer

Abstract: Novel eco-friendly fibrous materials with complex activities from cellulose acetate and cellulose acetate/polyethylene glycol (CA,PEG) containing 5-chloro-8-hydroxyquinoline as a model drug were obtained by electrospinning. Several methods, including scanning electron microscopy, X-ray diffraction analysis, ultraviolet-visible spectroscopy, water contact angle measurements, and mechanical tests, were utilized to characterize the obtained materials. The incorporation of PEG into the fibers facilitated the drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The results from in vitro release experiments demonstrate that the release of 5N was facilitated by the presence of water-soluble PVP or PVA on the surface of the fibrous material. The acquired results are consistent with our previous reports on how the presence of a water-soluble polymer in the fiber or on its surface increases the drug release rate [17,18,29,30,33].…”
Section: Drug Releasesupporting
confidence: 92%
See 2 more Smart Citations
“…The results from in vitro release experiments demonstrate that the release of 5N was facilitated by the presence of water-soluble PVP or PVA on the surface of the fibrous material. The acquired results are consistent with our previous reports on how the presence of a water-soluble polymer in the fiber or on its surface increases the drug release rate [17,18,29,30,33].…”
Section: Drug Releasesupporting
confidence: 92%
“…In the present study, the following approaches were applied to fabricate innovative fibrous materials loaded with a biologically active substance-5N-with a diverse design: the one-step electrospinning of CA and 5N-in-CA fibers from a solution of CA or CA/5N (Figure 1a,b) and the electrospinning of a CA/5N solution with the simultaneous electrospraying of solution of PVA,5N or PVP,5N (Figure 1c,d). Previously, we conducted a series of preliminary experiments to determine the optimal polymer concentration for the electrospinning of cellulose acetate [30]. It was found that defect-free fibers were obtained at a cellulose acetate concentration of 10 wt% in an acetone/water (80/20 v/v) solvent system.…”
Section: Preparation and Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, aromatic heterocyclic compounds from the group of 8-hydroxyquinoline, which have useful properties—antibacterial, antifungal, antitumor, antioxidant, anti-inflammatory and antiviral—and are characterized by low toxicity [ 31 , 32 , 33 , 34 ], have been studied intensively. Previously, we have reported on the incorporation of 8-hydroxyquinoline derivatives into electrospun materials from synthetic polymers [ 35 , 36 , 37 ], chitosan and its derivatives [ 19 , 38 ] and other natural polymers [ 39 , 40 ]. We have also reported the chemical immobilization of 5-amino-8-hydroxyquinoline onto the surface of electrospun fibers from styrene/maleic anhydride copolymers [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, electrospun nano-and microfibers have been widely used in the pharmaceutical field. 16 A variety of bioactive compounds and drugs including antibiotics, 17 proteins, 18 extracts, 19,20 DNA, 21 RNA 21 and anticancer drugs 22,23 have been loaded into electrospun nanofibers for disease treatment. Natural products can be obtained from four main sources: plants, animals, marine organisms and microorganisms.…”
Section: Introductionmentioning
confidence: 99%